Powder injection moulding of light alloys powder - (:unkn) unknown (European Powder Metallurgy Association (EPMA), 2011)
This paper describes the microstructural and mechanical properties of injection molded of Al and Ti6Al4V (Ti64) materials. Al and Ti64 powders were injection molded with wax-based binder. The critical powder loading for injection moulding was 62.5 - 67.5 vol. %.Binder debinding was performed in solvent and thermal method under high purity argon atmosphere. After debinding the samples were sintered at different temperatures and times in high purity argon and vacuum atmosphere (10-4 torr). The performances of the sintered parts were characterized using tensile testing, hardness testing, optical microcopy (OM) and scanning electron microscopy (SEM). The strengths and weaknesses of the test conditions have been analyzed from the densification behavior, microstructure, and mechanical properties. The results show that Al and Ti64 powders could be sintered to a maximum 96.2% and 99% of theoretical density. Maximum ultimate tensile strength and hardness were obtained 126 MPa, 46 HB at 650 °C for 2 hours for Al powder and 704 MPa, 38.6 HRC at 1275 °C for 10 hours for Ti64 alloys.